Secondary battery and electronic device
By using graphite particles with specific porosity and optimized electrolyte additives in secondary batteries, the volatility and flammability of the electrolyte is solved, the internal short circuit risk is reduced, and the capacity stability and flame retardant performance of the battery are improved.
Patent Information
- Application Number
- CN202510384571.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-04-25
AI Technical Summary
The electrolyte of existing secondary batteries has problems of volatile and flammability, resulting in low safety and the addition of high-content flame retardant will reduce the charge and discharge cycle characteristics.
Graphite particles with specific porosity are used as the negative electrode active substance, and combined with optimized electrolyte additives, the flame retardant performance of the electrolyte is improved, the contact area between the electrolyte and the negative electrode active material is reduced, and the electron conductivity in the contact area is reduced, thereby reducing the occurrence of internal short circuits.
The capacity attenuation problem of secondary batteries in the charging and storage state is improved, and it has excellent flame retardant performance and excellent charge and discharge cycle performance.
Smart Images

Figure SMS_13 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] The present application relates to a negative electrode for a secondary battery and an electrolyte for a secondary battery, and in particular to a secondary battery and an electronic device. Background Art
[0002] With the rapid popularization of electronic devices, the performance requirements for secondary batteries are increasing, especially in terms of safety and cycle stability. Currently, the commonly used electrolytes have the problems of volatility and flammability, resulting in low safety during use; although adding high levels of flame retardants can improve flame retardancy, it often reduces the battery's charge and discharge cycle characteristics. Summary of the invention
[0003] In view of this, the present application provides a secondary battery and an electronic device, which have excellent flame retardant properties and excellent charge and discharge cycle performance.
[0004] In a first aspect, an embodiment of the present application provides a secondary battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector; the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a first graphite particle and a second graphite particle; wherein the porosity of the first graphite particle is 7% to 14.5%, and the porosity of the second graphite particle is 0.1% to 3.5%; The electrolyte includes a first additive and a second additive, wherein the first additive includes at least one of the compounds shown in Formula 1-1 to Formula 1-3: Formula 1-1, Formula 1-2, Formula 1-3; The second additive includes at least one of the compounds shown in Formula 2-1 to Formula 2-2: Formula 2-1, Formula 2-2.
[0005] The present application adopts graphite particles with a specific porosity as the negative electrode active material, and combines them with optimized electrolyte additives, which not only improves the flame retardant properties of the electrolyte, but also effectively controls the contact area between the electrolyte and the negative electrode active material, while reducing the electronic conductivity of the contact area, thereby reducing the occurrence of internal short circuits and improving the capacity attenuation problem of the secondary battery in the charging and storage state, thereby having excellent flame retardant properties while having excellent charge and discharge cycle performance.
[0006] In some embodiments, the porosity of the first graphite particles is preferably 7.5% to 12.5%; the porosity of the second graphite particles is preferably 0.7% to 2.4%. This can further improve the problem of capacity reduction of the secondary battery during charge storage and improve its cycle life.
[0007] In some embodiments, based on the mass of the electrolyte, the mass ratio of the first additive is 1% to 7%. When the content of the first additive is within the above range, the additive can promote the formation of a stable film with excellent ion-conducting performance but general electron-conducting performance on the surface of the negative electrode active material. This film not only effectively reduces the side reactions and physical contact between the electrode and the electrolyte, but also reduces the risk of internal short circuit, thereby improving the capacity attenuation problem of the secondary battery in the charge storage state. At the same time, this stable interfacial film can also optimize the long-cycle performance of the battery, further improving its service life, enabling the battery to maintain excellent electrochemical stability and cycle durability while having high safety.
[0008] In some embodiments, based on the mass of the electrolyte, the mass ratio of the second additive is 0.1% to 2.5%. When the content of the second additive is within the above range, the additive can promote the formation of a stable film with excellent ion-conducting performance but general electron-conducting performance on the surface of the negative electrode active material. This film not only effectively reduces the side reactions and physical contact between the electrode and the electrolyte, but also reduces the risk of internal short circuit, thereby improving the capacity attenuation problem of the secondary battery in the charge storage state. At the same time, this stable interfacial film can also optimize the long-cycle performance of the battery, further improving its service life.
[0009] In some embodiments, the negative electrode active material layer is bisected in the thickness direction, including an inner region close to the negative electrode current collector and an outer region far from the negative electrode current collector. Among them, the content of the first graphite particles in the outer region is a1, and the content of the first graphite particles in the inner region is a2, satisfying: a1 > a2. In this application, by making the content of the first graphite particles in the outer region higher than that in the inner region, more active ions can be stored in the outer region, thereby ensuring that the battery maintains high capacity and stable electrochemical performance during long cycles.
[0010] In some embodiments, the content of the second graphite particles in the outer region is a3, and the content of the second graphite particles in the inner region is a4, satisfying: a3 < a4. Compared with the outer region, the content of the second graphite particles in the inner region is higher. This design can form an efficient ion transport channel inside the active layer, thereby quickly transporting active ions, optimizing the distribution and insertion / extraction behavior of lithium ions in the electrode, and thus ensuring that the battery maintains high capacity and stable electrochemical performance during long cycles.
[0011] In some embodiments, the mass ratio of the first graphite particles to the second graphite particles in the outer region is 75: 25 to 100: 0. The present application can further optimize the structural stability and ion transfer efficiency of the electrode while ensuring that the outer region has a high active ion storage capacity by regulating the ratio of the first graphite particles to the second graphite particles in the outer region within the above range, thereby ensuring that the battery maintains high capacity and stable electrochemical performance during a long cycle.
[0012] In some embodiments, the first additive comprises Formula 1-3; Formula 1-3.
[0013] When the first additive includes the compound of formula 1-3, it can promote the formation of a stable film with better ion conductivity but average electron conductivity on the surface of the negative electrode active material. This film not only effectively reduces the side reaction and physical contact between the electrode and the electrolyte, but also reduces the risk of internal short circuit, thereby further improving the capacity attenuation problem of the secondary battery in the charging storage state.
[0014] In some embodiments, the positive electrode includes a positive electrode current collector, a positive electrode active material layer disposed on the surface of the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material; the positive electrode active material includes a nickel-containing oxide represented by Chemical Formula 1; Chemical formula 1 is Li a Ni b M c N d O 2-m Q m ; Wherein, in Chemical Formula 1, 0.9≤a≤1.8, 0.7≤b≤1, 0≤c≤0.3, 0≤d≤0.3, 0.9≤b+c+d≤1.1, and 0≤m≤0.1; M and N are each independently selected from at least one element of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W and Zr; Q is at least one element selected from F, P and S. By adopting such a positive electrode active material with a high nickel content, it is possible not only to achieve high capacity of the secondary battery during a long cycle, but also to further improve its cycle stability and safety.
[0015] A second aspect of the present application provides an electronic device, comprising the above-mentioned secondary battery.
[0016] Compared with the prior art, this application has the following beneficial effects: The present application adopts graphite particles with a specific porosity as the negative electrode active material, and combines them with optimized electrolyte additives, which not only improves the flame retardant properties of the electrolyte, but also reduces the contact area between the electrolyte and the negative electrode active material, while reducing the electronic conductivity of the contact area between the two, thereby reducing the occurrence of internal short circuits and improving the capacity attenuation problem of the secondary battery in the charged storage state, thereby having both excellent flame retardant properties and excellent charge and discharge cycle performance. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.
[0018] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the implementation or examples are included in at least one implementation or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same implementation or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more implementations or examples in a suitable manner.
[0019] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0020] In this application, unless otherwise specified, the contents are measured by mass.
[0021] According to the first aspect of the present application, the present application provides a secondary battery, which includes a negative electrode, a positive electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode. The secondary battery can be a common battery in the art that can be used continuously by activating the active material by charging after the battery is discharged; in some embodiments, the secondary battery includes but is not limited to a lithium-ion battery.
[0022] In the present application, the electrolyte comprises a base solvent and an additive. The negative electrode comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The positive electrode comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector.
[0023] This application mainly aims at making special improvements and limitations on the formula content of the electrolyte and the negative electrode active material (graphite) of the negative electrode to obtain a secondary battery with stable performance.
[0024] Specifically, the negative electrode includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector; the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes a first graphite particle and a second graphite particle; wherein the porosity of the first graphite particle is 7% to 14.5%, and the porosity of the second graphite particle is 0.1% to 3.5%; The electrolyte includes a first additive and a second additive, wherein the first additive includes at least one of the compounds shown in Formula 1-1 to Formula 1-3: Formula 1-1, Formula 1-2, Formula 1-3; The second additive includes at least one of the compounds shown in Formula 2-1 to Formula 2-2: Formula 2-1, Formula 2-2.
[0025] As an example, the porosity of the first graphite particles may be 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 14.5%, etc., or a value within a range consisting of any two of these values.
[0026] As an example, the porosity of the second graphite particles may be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, etc., or a value within a range composed of any two of these values.
[0027] The inventors have discovered through research that in secondary batteries, by using graphite particles with a specific porosity as the negative electrode active material and combining them with optimized electrolyte additives, not only the flame retardant properties of the electrolyte are improved, but also the contact area between the electrolyte and the negative electrode active material can be effectively controlled, while reducing the electronic conductivity of the contact area, thereby reducing the occurrence of internal short circuits and improving the capacity attenuation problem of the secondary battery in the charged storage state, thereby having both excellent flame retardant properties and excellent charge and discharge cycle performance.
[0028] In some embodiments, the porosity of the first graphite particles is preferably 7.5% to 12.5%. As an example, the porosity of the first graphite particles can be 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11.5%, 12.5%, etc. or a value within a range composed of any two of these values. The capacity reduction problem of the secondary battery in the charged storage state can be further improved, and its long cycle life can be improved.
[0029] In some embodiments, the porosity of the second graphite particles is preferably 0.7% to 2.4%. As an example, the porosity of the second graphite particles can be 0.7%, 0.9%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.4%, etc. or a value within a range composed of any two of these values. The capacity reduction problem of the secondary battery in the charged storage state can be further improved, and its long cycle life can be improved.
[0030] In some embodiments, based on the mass of the electrolyte, the mass proportion of the first additive is 1% to 7%. As an example, based on the mass of the electrolyte, the mass proportion of the first additive can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, etc. or a value within the range of any two of these values. When the content of the first additive is within the above range, the additive can form a stable film with excellent ion conductivity but general electronic conductivity on the surface of the negative electrode active material. This film not only effectively reduces the side reactions and physical contact between the electrode and the electrolyte, but also reduces the risk of internal short circuits, thereby improving the capacity attenuation problem of the secondary battery in the charged storage state. At the same time, this stable interface film can also optimize the long cycle performance of the battery, further improve its service life, and enable the battery to maintain excellent electrochemical stability and cycle durability while having high safety.
[0031] In some embodiments, based on the mass of the electrolyte, the mass proportion of the second additive is 0.1% to 2.5%. As an example, based on the mass of the electrolyte, the mass proportion of the second additive is 0.1%, 0.5%, 0.8%, 1%, 1.5%, 1.8%, 2.0%, 2.3%, 2.5%, etc. or a value within the range of any two of these values. When the content of the second additive is within the above range, the additive can form a layer of stable film with excellent ion conductivity but general electronic conductivity on the surface of the negative electrode active material. This film not only effectively reduces the side reactions and physical contact between the electrode and the electrolyte, but also reduces the risk of internal short circuits, thereby improving the capacity attenuation problem of the secondary battery in the charged storage state. At the same time, this stable interface film can also optimize the long cycle performance of the battery and further improve its service life.
[0032] In some embodiments, the negative electrode active material layer is divided into two equal parts in the thickness direction, including an inner region close to the negative electrode current collector and an outer region away from the negative electrode current collector, wherein the content of the first graphite particles contained in the outer region is a1, and the content of the first graphite particles contained in the inner region is a2, satisfying: a1>a2. In the present application, by making the content of the first graphite particles in the outer region higher than that in the inner region, more active ions can be stored in the outer region, thereby ensuring that the battery maintains high capacity and stable electrochemical performance during a long cycle.
[0033] In some embodiments, the content of the second graphite particles in the outer region is a3, and the content of the first graphite particles in the inner region is a4, satisfying: a3 < a4. Compared with the outer region, the content of the second graphite particles in the inner region is higher. This design can form an efficient ion transport channel inside the active layer, thereby quickly transporting active ions, optimizing the distribution and insertion / extraction behavior of lithium ions in the electrode, and thus ensuring that the battery maintains high capacity and stable electrochemical performance during long-term cycling.
[0034] In some embodiments, the mass ratio of the first graphite particles to the second graphite particles in the outer region is from 75:25 to 100:0. As an example, the mass ratio of the first graphite particles to the second graphite particles in the outer region is 75:25, 80:20, 85:15, 90:10, 95:5, 100:0, etc., or values within the range composed of any two of these values. By regulating the ratio of the first graphite particles to the second graphite particles in the outer region within the above range, the present application can further optimize the structural stability and ion transport efficiency of the electrode while ensuring that the outer region has a high active ion storage capacity, thereby ensuring that the battery maintains high capacity and stable electrochemical performance during long-term cycling.
[0035] In some embodiments, the first additive includes Formula 1-3; Formula 1-3.
[0036] When the first additive includes a compound of Formula 1-3, a stable film with excellent ion conduction performance but general electron conduction performance can be jointly formed on the surface of the negative electrode active material. This film not only effectively reduces the side reactions and physical contact between the electrode and the electrolyte, but also reduces the risk of internal short circuit, thereby improving the problem of capacity attenuation of the secondary battery in the charged storage state.
[0037] In some embodiments, the positive electrode active material includes a nickel-containing oxide represented by Chemical Formula 1; Chemical Formula 1 is Li a Ni b M c N d O 2-m Q m ; wherein, in Chemical Formula 1, 0.9 ≤ a ≤ 1.8, 0.7 ≤ b ≤ 1, 0 ≤ c ≤ 0.3, 0 ≤ d ≤ 0.3, 0.9 ≤ b + c + d ≤ 1.1, and 0 ≤ m ≤ 0.1; M and N are each independently at least one element selected from Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W and Zr; Q is at least one element selected from F, P and S. As an example, in Chemical Formula 1, a may be 0.9, 1.0, 1.2, 1.3, 1.5, 1.7, 1.8, etc., or a value in the range of any two of these values. As an example, in Chemical Formula 1, b may be 0.7, 0.8, 0.9, 1, etc., or a value in the range of any two of these values. As an example, in Chemical Formula 1, c may be 0, 0.1, 0.2, 0.3, etc., or a value in the range of any two of these values. As an example, in Chemical Formula 1, d may be 0, 0.1, 0.2, 0.3, etc., or a value in the range of any two of these values. By adopting the above-mentioned positive electrode active material with a high nickel content, not only can the secondary battery maintain a high capacity during a long cycle, but its cycle stability and safety can also be further improved.
[0038] Electrolyte In addition to the above-mentioned additives, the electrolyte further includes an organic solvent, which may be, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate, propyl propionate, ethyl propionate, or methyl propionate. In some embodiments, other organic solvents include ether solvents, such as at least one of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME).
[0039] In the embodiment of the present application, the electrolyte includes a lithium salt as an electrolyte. The lithium salt in the electrolyte includes, but is not limited to: inorganic lithium salts, such as LiClO4, LiAsF6, LiPF6, LiBF4, LiSbF6, LiSO3F, LiN(FSO2)2; fluorine-containing organic lithium salts, such as LiCF3SO3, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,3-hexafluoropropane disulfonyl imide lithium, cyclic 1,2-tetrafluoroethane disulfonyl imide lithium, LiPF4(CF3)2, LiN(CF3SO2) (C4F9SO2), LiC(CF3SO2)3, LiPF4(CF3SO2)2, LiPF4(C2F5)2, LiPF4(C2F5SO2)2, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, LiBF2(C2F5SO2)2; lithium salts containing dicarboxylic acid complexes, such as lithium bis(oxalato)borate, lithium difluorooxalatoborate, lithium tris(oxalato)phosphate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate. In addition, the above-mentioned lithium salts can be used alone or in combination of two or more. For example, in some embodiments, the lithium salt comprises a combination of LiPF6 and LiBF4. In some embodiments, the lithium salt comprises LiPF6. In some embodiments, based on the mass of the electrolyte, the mass proportion of the lithium salt in the electrolyte is 10% to 20%.
[0040] The electrolyte also includes other additives. The additives that can be used in the electrolyte of the present application embodiment can be additives that are well known in the art and can be used to improve the electrochemical performance of the battery. In some embodiments, the additive includes, but is not limited to, at least one of polynitrile compounds, sulfur-containing additives, fluoroethylene carbonate (FEC), and 1,4-butane sultone.
[0041] The preparation method of the electrolyte in the embodiment of the present application is not limited and can be obtained according to the conventional preparation method of the electrolyte in the industry.
[0042] negative electrode In some embodiments, the first graphite particles and the second graphite particles include at least one of artificial graphite or natural graphite. Preferably, at least a portion of the surface of the first graphite particles is coated with amorphous carbon. Thus, the high rate charge and discharge capacity of the secondary battery is further improved.
[0043] The first graphite particles can be obtained by the following preparation method: crushing the coke raw material into a certain particle size, using a binder to condense to obtain a mixture, graphitizing the mixture at a temperature above 2600°C, and screening to obtain the first graphite particles. According to the particle size of the crushed raw material, the particle size of the mixture, etc., the porosity of the first graphite particles can be adjusted to 7% to 14.5%. For example, the particle size Dv50 of the crushed raw material is preferably 11μm to 18μm. The porosity of the first graphite particles can be reduced by increasing the particle size of the crushed raw material.
[0044] The second graphite particles can be obtained by the following preparation method: crushing the coke raw material into a certain particle size, using a binder to condense to obtain a mixture, pressurizing the mixture into a block mixture, graphitizing the block mixture at a temperature above 2600°C, and crushing and screening the graphitized block mixture to obtain the second graphite particles. The porosity of the second graphite particles can be adjusted to 0.1% to 3.5% by adjusting the amount of volatiles in the mixture, such as a binder (such as asphalt) added to the coke raw material.
[0045] In some embodiments, the negative electrode active material may include a silicon-based material, such as a silicon-carbon material and / or a silicon-oxygen material, in addition to the first and second graphite particles used in the present application. In the negative electrode active material layer having the negative electrode active material including the first and second graphite particles, the contact point with the silicon-based material needs to be increased, thereby easily ensuring the contact point with the expansion and contraction of the Si-based material, ensuring the conductivity and the capacity of the secondary battery. Based on the mass of the negative electrode active material layer, the mass proportion of the silicon-based material is 1% to 10%, preferably 3% to 7%.
[0046] In some embodiments, the negative electrode active material layer further comprises a binder. The binder may include various binder polymers, such as polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.
[0047] In some embodiments, the negative electrode active material layer further comprises a conductive agent to improve the electrode conductivity. Any conductive material can be used as the conductive material as long as it does not cause chemical changes. Examples of conductive agents include, but are not limited to: carbon-based materials, such as carbon black, acetylene black, Ketjen black, carbon fibers, etc.; metal-based materials, such as metal powders or metal fibers including copper, nickel, aluminum, silver, etc.; conductive polymers, such as polyphenylene derivatives, etc.; or mixtures thereof.
[0048] In some embodiments, the negative electrode current collector includes, but is not limited to: copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and any combination thereof. In some embodiments, the negative electrode current collector is copper foil.
[0049] In some embodiments, the preparation method of the negative electrode is a method for preparing a negative electrode that can be used for an electrochemical device that is well known in the art. Exemplarily, the negative electrode can be obtained by the following method: mixing the active material, the conductive agent, the binder and the above-mentioned negative electrode additive in a solvent, and heating the thickener as needed to prepare a negative electrode active material slurry, and coating the negative electrode active material slurry on the current collector, drying, and cold pressing to form a negative electrode active material layer. In some embodiments, the solvent may include, but is not limited to, water, N-methylpyrrolidone.
[0050] positive electrode The positive electrode includes a positive electrode collector and a positive electrode active material layer disposed on at least one surface of the positive electrode collector.
[0051] In some embodiments, the positive electrode active material includes a nickel-containing oxide represented by Chemical Formula 1; Chemical formula 1 is Li a Ni b M c N d O 2-m Q m ; Wherein, in Chemical Formula 1, 0.9≤a≤1.8, 0.7≤b≤1, 0≤c≤0.3, 0≤d≤0.3, 0.9≤b+c+d≤1.1, and 0≤m≤0.1; M and N are each independently selected from at least one element of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W and Zr; Q is at least one element selected from F, P and S. By adopting such a positive electrode active material with a high nickel content, it is possible not only to achieve high capacity of the secondary battery during a long cycle, but also to further improve its cycle stability and safety.
[0052] In some embodiments, the positive electrode active material may also include Li x CoO2、Li x MnO2、Li x Mn2O4、Li x Mn 2- y M yO4, LiMPO4, Li2MPO4F (M: at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9). These may be used alone or in combination of two or more.
[0053] In some embodiments, the positive electrode active material layer further includes a binder and optionally a conductive material. The binder can improve the bonding between the positive electrode active material particles and can improve the bonding between the positive electrode active material and the positive electrode current collector. In some embodiments, the binder includes, but is not limited to, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin and nylon, etc.
[0054] In some embodiments, the positive electrode active material layer also includes a conductive material to impart conductivity to the electrode. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., carbon black, acetylene black, ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0055] In some embodiments, the positive electrode current collector is a metal, such as but not limited to aluminum foil.
[0056] In some embodiments, the preparation method of the positive electrode is a preparation method of the positive electrode that can be used for a secondary battery that is well known in the art. For example, the positive electrode can be obtained by the following method: mixing a positive electrode active material, a conductive material, and a binder in a solvent to prepare a positive electrode active material slurry, and coating the positive electrode active material slurry on a current collector, drying, and cold pressing to form a positive electrode active material layer. In some embodiments, the solvent may include water, N-methylpyrrolidone, etc., but is not limited thereto.
[0057] Isolation film In some embodiments, a separator is provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0058] For example, in some embodiments, the isolation film includes a substrate layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure. The material of the substrate layer can be selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, the material of the substrate layer can be selected from polypropylene porous film, polyethylene porous film, polypropylene non-woven fabric, polyethylene non-woven fabric or polypropylene-polyethylene-polypropylene porous composite film.
[0059] A surface treatment layer is provided on at least one surface of the substrate layer. The surface treatment layer can be a polymer layer, an inorganic layer or a layer formed by a mixed polymer and an inorganic substance. Specifically, the inorganic layer includes inorganic particles and a binder. The inorganic particles can be selected from one or more combinations of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The binder can be selected from one or more combinations of polyvinylidene fluoride, a polymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.
[0060] According to a second aspect of the present application, the present application provides an electronic device, which includes the above-mentioned secondary battery.
[0061] The use of the secondary battery of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. For example, the electronic device includes, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc. In addition, the secondary battery of the present application is applicable to energy storage power stations, sea transport vehicles, and air transport vehicles in addition to the electronic devices listed above. Air transport vehicles include air transport vehicles within the atmosphere and air transport vehicles outside the atmosphere.
[0062] The technical solutions of the embodiments of the present application are further described below through specific examples. Unless otherwise specified, the raw materials used in the following examples are all from common commercial products, and the devices or equipment used are all purchased from conventional market sales channels.
[0063] Example Below, taking lithium-ion batteries as an example, examples and comparative examples are given to explain the implementation of the secondary battery of the present application in more detail. Those skilled in the art will understand that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are mass references.
[0064] Example 1 1. Preparation of lithium-ion batteries: 1. Preparation of negative electrode: Step 1, preparation of first graphite particles: controlling the particle size of coke to Dv50 of 8 μm, adding binder asphalt to the coke to obtain a mixture with Dv50 of 11 μm, high-temperature graphitizing the mixture at a temperature of 2800°C, and sieving to obtain first graphite particles with Dv50 of 13 μm and a porosity of 11.5%; Step 2: Preparation of the second graphite particles: The particle size of the coke is controlled to be 11.5 μm in Dv50, a binder pitch is added to the coke to solidify it, and pressure is applied to obtain a density of 1.65 g / cm 3 The block was graphitized at 2800°C. The graphitized block was granulated and sieved to obtain second graphite particles with a Dv50 of 13.5 μm and a porosity of 1.0%.
[0065] Step 3: Add the first graphite particles, second graphite particles, conductive carbon black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) prepared above to deionized water in a mass ratio of 81.6:14.4:1.5:1.5:1, and stir and mix thoroughly to form a uniform first negative electrode slurry; Add the first graphite particles, second graphite particles, conductive carbon black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) prepared above to deionized water in a mass ratio of 13:83:1.5:1.5:1, and stir and mix thoroughly to form a uniform second negative electrode slurry. The second negative electrode slurry is evenly coated on both sides of the negative electrode current collector copper foil, and after drying, the first negative electrode slurry is evenly coated on the surfaces of the second negative electrode slurry on both sides and dried, and the thickness of the first negative electrode slurry and the second negative electrode slurry coated on one side of the negative electrode current collector are the same. After cold pressing, the negative electrode active material layer is formed, and then the negative electrode is obtained by cutting and welding the electrode ears.
[0066] 2. Preparation of positive electrode: The positive electrode active material LiNi 0.8 Co 0.12 Al 0.13 O 1.95 P 0.05, acetylene black as a conductive agent, and polyvinylidene fluoride (PVDF) as a binder are mixed in a solvent N-methylpyrrolidone (NMP) at a mass ratio of 96.3:2.2:1.5, and stirred evenly in a vacuum mixer to obtain a positive electrode slurry. The positive electrode material is coated on the positive electrode current collector aluminum foil, dried, and cold pressed to form a positive electrode active material layer, and then cut into pieces and welded to the pole ears to obtain the positive electrode.
[0067] 3. Preparation of electrolyte: In a dry argon atmosphere glove box, propyl propionate (PP), ethyl propionate (EP), ethylene carbonate (EC), and propylene carbonate (PC) were mixed evenly, dissolved and fully stirred, and then the first additive, the second additive, and the lithium salt LiPF6 were added and mixed evenly to obtain an electrolyte. Based on the mass of the electrolyte, the mass proportions of the first additive and the second additive are shown in Table 1, the mass proportion of the lithium salt LiPF6 is 12.5%, the mass proportion of EP is 20%, the mass proportion of PP is 40%, and the remainder is ethylene carbonate (EC) and propylene carbonate (PC), and the mass ratio of EC to PC is EC:PC=2.1:1.1.
[0068] 4. Preparation of isolation membrane: Polyethylene (PE) porous polymer film is used as the isolation membrane.
[0069] 5. Preparation of lithium-ion batteries: The obtained positive electrode, isolation film, and negative electrode are stacked in order, so that the isolation film is placed between the positive electrode and the negative electrode to play an isolating role, and then wound to obtain a bare cell; the bare cell is placed in an outer packaging foil aluminum-plastic film, and the electrolyte is injected. After vacuum packaging, standing, formation and other process flows, a lithium-ion battery is obtained.
[0070] The preparation processes of Examples 2 to 22 and Comparative Examples 1 to 4 are substantially the same as those of Example 1. For specific differences, please refer to Table 1.
[0071] Embodiment 23 The difference between this embodiment and embodiment 1 is that step 3 of <preparation of negative electrode> in this embodiment is as follows: Step 3: Add the first graphite particles, second graphite particles, conductive carbon black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) prepared above to deionized water in a mass ratio of 48:48:1.5:1.5:1, and stir and mix thoroughly to form a uniform first negative electrode slurry; Add the first graphite particles, second graphite particles, conductive carbon black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) prepared above to deionized water in a mass ratio of 48:48:1.5:1.5:1, and stir and mix thoroughly to form a uniform second negative electrode slurry. The second negative electrode slurry is evenly coated on both sides of the negative electrode current collector copper foil, and after drying, the first negative electrode slurry is evenly coated on the surfaces of the second negative electrode slurry on both sides and dried, and the thickness of the first negative electrode slurry and the second negative electrode slurry coated on one side of the negative electrode current collector are the same. After cold pressing, the negative electrode active material layer is formed, and then the negative electrode is obtained by cutting and welding the electrode ears. The rest is the same as in Example 1.
[0072] 2. Test Method 1. Flame retardancy test of electrolyte: 2 ml of each electrolyte was infiltrated into glass fiber (20 mm wide x 65 mm long), and then exposed to the test flame in the air for 10 seconds. After that, the test flame was moved away, and the flame state was observed with the naked eye. The time until the fire was extinguished was measured. If the time to extinguish the fire was less than 10 seconds, it was determined to be flame retardant, and if it was more than 10 seconds, it was determined to be combustible.
[0073] 2. Discharge capacity maintenance rate after storage: At a temperature of 25°C, the lithium-ion battery was charged at a constant voltage of 4.1V for 5 hours, and then discharged at a current value of 1.0C to a termination voltage of 2.7V, and the discharge capacity C0 was tested. At a temperature of 25°C, the lithium-ion battery was charged at a constant voltage of 4.1V for 5 hours, and then placed at a temperature of 50°C for 30 days, and then discharged at a current value of 1.0C to a termination voltage of 2.7V, and the discharge capacity C1 was tested. The discharge capacity maintenance rate after placement is R=C1 / C0.
[0074] A: 90%≤R≤95%; B: 85%≤R<90%; C: 80%≤R<85%; D: 75%≤R<80%; E: Less than 70%.
[0075] Table 1
[0076] Analysis of results: It can be seen from Table 1 that the electrolyte additive combination used in the present application has graphite particles with a specific porosity as the negative electrode active material, which can improve the flame retardancy of the electrolyte, and reduce the internal short circuit of the secondary battery by reducing the contact area between the electrolyte and the negative electrode active material and reducing the electronic conductivity during contact, thereby improving the capacity reduction of the secondary battery in the charged storage state.
[0077] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.
Claims
1. A secondary battery comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The negative electrode comprises a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector; the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a first graphite particle and a second graphite particle; wherein the porosity of the first graphite particle is 7% to 14.5%, and the porosity of the second graphite particle is 0.1% to 3.5%; The electrolyte includes a first additive and a second additive, wherein the first additive includes at least one of the compounds represented by Formula 1-1 to Formula 1-3: Formula 1-1, Formula 1-2, Formula 1-3; The second additive includes at least one of the compounds shown in Formula 2-1 to Formula 2-2: Formula 2-1, Formula 2-2.
2. The secondary battery according to claim 1, characterized in that: Based on the mass of the electrolyte, the mass of the first additive accounts for 1% to 7%.
3. The secondary battery according to claim 1, characterized in that: Based on the mass of the electrolyte, the mass proportion of the second additive is 0.1% to 2.5%.
4. The secondary battery according to claim 1, characterized in that: The negative electrode active material layer is divided into two equal parts in the thickness direction, including an inner region close to the negative electrode current collector and an outer region away from the negative electrode current collector, wherein the content of the first graphite particles contained in the outer region is a1, and the content of the first graphite particles contained in the inner region is a2, satisfying: a1>a2.
5. The secondary battery according to claim 4, characterized in that: The content of the second graphite particles in the outer region is a3, and the content of the second graphite particles in the inner region is a4, satisfying: a3 <a4。 6. The secondary battery according to claim 4, characterized in that: A mass ratio of the first graphite particles to the second graphite particles in the outer region is 75:25 to 100:
0.
7. The secondary battery according to claim 1, characterized in that: The first additive comprises formula 1-3; Formula 1-3.
8. The secondary battery according to claim 1, characterized in that: The positive electrode comprises a positive electrode current collector and a positive electrode active material layer disposed on the surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material; the positive electrode active material comprises a nickel-containing oxide represented by Chemical Formula 1; Chemical formula 1 is Li a Ni b M c N d O 2-m Q m ; Wherein, in Chemical Formula 1, 0.9≤a≤1.8, 0.7≤b≤1, 0≤c≤0.3, 0≤d≤0.3, 0.9≤b+c+d≤1.1, and 0≤m≤0.1; M and N are each independently selected from at least one element of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W and Zr; Q is selected from at least one element of F, P and S.
9. The secondary battery according to any one of claims 1 to 8, characterized in that: The porosity of the first graphite particles is 7.5% to 12.5%.
10. An electronic device, characterized in that: It includes the secondary battery according to any one of claims 1 to 9.
Citation Information
Patent Citations
Non-aqueous electrolyte secondary battery
CN113474914A
Rechargeable lithium battery
CN119381554A
Nonaqueous electrolyte and lithium ion secondary battery
JP2016018708A
Adapter for voltage watt hour meter for securing safety of workers
KR1020250026793A
Non-aqueous electrolyte secondary battery
WO2024070220A1